Model Manajemen SDM Publik Berbasis Kompetensi Digital dan Etika Pelayanan Publik (Studi Konseptual pada Dinas Kepegawaian Kota Gorontalo) - Nggilu, Rukiah; Mokodongan, Regi (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2026)
Digital transformation has fundamentally reshaped human resource management (HRM) in the public sector, requiring civil servants to possess not only technological competence but also strong ethical values in public service delivery. This study aims to reconstruct a public HRM model based on digital competencies and public service ethics. Using a conceptual approach, this article employs critical literature synthesis on public sector HRM, digital competencies of civil servants, and public service ethics. The findings reveal a significant gap between the enhancement of digital competencies and the internalization of ethical values in bureaucratic practices, particularly within the Gorontalo City Civil Service Agency. This study proposes an integrative model linking digital competence, public service ethics, adaptive organizational culture, and transformational leadership. The model provides a strategic foundation for developing ethical, adaptive, and human-centered public human resource policies in the era of digital government.